Hagyjátok Robinsont! The hungarian-cuban interpretation of Daniel Defoe’s novel and other film adaptations of Robinson Crusoe - Bubak, Grzegorz (Porównania, 2019)
The story of Robinson Crusoe has been told many times in the film, sometimes with faithfulness to the literary original, more often with numerous deviations and more or less ingenious variants. The creators of various ranks and authority inscribed the hero’s adventures in numerous genre schemes, ranging - in the most natural way - from adventure film to comedy and science fiction. It was Daniel Deofe’s story that provided the inspiration rather than the prototype of his hero – Alexander Selkirk. Interestingly, far-reaching transcripts of Robinson’s adventures already appeared in the 1930s. Little is known about what had happened before. The movies about which any information can be found are usually considered missing. In the paper, I write about the Hungarian-Cuban version of the adventures of Robinson Crusoe and about other films that could have been to some extent an inspiration for director Péter Tímár.